2020
DOI: 10.1093/plankt/fbaa060
|View full text |Cite
|
Sign up to set email alerts
|

Annual phytoplankton succession results from niche-environment interaction

Abstract: Annual plankton succession has been investigated for many decades with hypotheses ranging from abiotic to biotic mechanisms being proposed to explain these recurrent patterns. Here, using data collected by the Continuous Plankton Recorder (CPR) survey and models originating from the MacroEcological Theory on the Arrangement of Life, we investigate Annual Phytoplankton Succession (APS) in the North Sea at a species level. Our results show that this phenomenon can be predicted well by models combining photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 89 publications
(87 reference statements)
1
39
0
Order By: Relevance
“…Recurring patterns in photosynthetic taxa succession along disturbance gradients reflect intricate interplays between transient environmental components and taxa‐specific functional traits, for instance, related to resource utilization (light and nutrients) and resilience to mortality factors (grazing, viral infections, etc. ; Sommer et al, 2012; Chang et al, 2019; Caracciolo et al, 2021). Over a spring‐to‐summer succession, from sympagic (sea‐ice) to planktonic growth forms, Arctic diatoms collectively exploit a wide range of environmental conditions through an extensive habitat shift: from dimly lit sea‐ice brines (<1 μmol photons m −2 s −1 and minimal photoperiod; Hancke et al, 2018) to intensely illuminated open waters (up to approximately 1000 μmol photons m −2 s −1 and 24 h daylight; Massicotte et al, 2020; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recurring patterns in photosynthetic taxa succession along disturbance gradients reflect intricate interplays between transient environmental components and taxa‐specific functional traits, for instance, related to resource utilization (light and nutrients) and resilience to mortality factors (grazing, viral infections, etc. ; Sommer et al, 2012; Chang et al, 2019; Caracciolo et al, 2021). Over a spring‐to‐summer succession, from sympagic (sea‐ice) to planktonic growth forms, Arctic diatoms collectively exploit a wide range of environmental conditions through an extensive habitat shift: from dimly lit sea‐ice brines (<1 μmol photons m −2 s −1 and minimal photoperiod; Hancke et al, 2018) to intensely illuminated open waters (up to approximately 1000 μmol photons m −2 s −1 and 24 h daylight; Massicotte et al, 2020; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…First, given that phytoplankton communities have short generation time (Reynolds 2006), the monthly resolution makes difficult to capture the turnover in species abundance rank at the finest possible scale. Studying the daily or even weekly variation in abundance rank would help us to disentangle the so‐called stochastic abundance fluctuations (Caracciolo et al 2021). However, it has been shown that the study of phytoplankton community processes on monthly to yearly time scales helps to understand the long‐term ecological and evolutive dynamics of communities (Segura et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…costatum had the highest optimum for nutrients concentration and MLD but the lowest for temperature and salinity, conditions indicative of the spring bloom over cold temperate continental shelves (Caracciolo et al, 2021; Table 1, Figure 3b). The lowest optimum for euphotic depth was found for R. styliformis (Table 1, Figure 3c).…”
Section: Estimates Of Niche Optimumsmentioning
confidence: 99%